Large-scale GWAS of food liking reveals genetic determinants and genetic correlations with distinct neurophysiological traits - May-Wilson, Sebastian; Matoba, Nana; Wade, Kaitlin H.; Hottenga, Jouke-Jan; Concas, Maria Pina; Mangino, Massimo; Grzeszkowiak, Eryk J.; Menni, Cristina; Gasparini, Paolo; Timpson, Nicholas J.; Veldhuizen, Maria G.; de Geus, Eco; et al. (Nature communications, 2022)
We present the results of a GWAS of food liking conducted on 161,625 participants from the UK-Biobank. Liking was assessed over 139 specific foods using a 9-point scale. Genetic correlations coupled with structural equation modelling identified a multi-level hierarchical map of food-liking with three main dimensions: “Highly-palatable”, “Acquired” and “Low-caloric”. The Highly-palatable dimension is genetically uncorrelated from the other two, suggesting that independent processes underlie liking high reward foods. This is confirmed by genetic correlations with MRI brain traits which show with distinct associations. Comparison with the corresponding food consumption traits shows a high genetic correlation, while liking exhibits twice the heritability. GWAS analysis identified 1,401 significant food-liking associations which showed substantial agreement in the direction of effects with 11 independent cohorts. In conclusion, we created a comprehensive map of the genetic determinants and associated neurophysiological factors of food-liking. Genetic determinants of food consumption and food liking are likely to be distinct, although it has not been well studied. Here, the authors identify genetic variants associated with food-liking, finding that different food-liking traits correlate with different brain areas and other food consumption traits.